Peran Filsafat Ilmu dalam Perkembangan Bahasa dan Implikasinya terhadap Pendidikan - Mardi, Melia; Putri, Desmimi Eka; Yasmanelly, Yasmanelly; Fauziati, Fauziati; Isesmazurita, Isesmazurita; Marsis, Marsis (Universitas Islam Sumatera Utara, 2025)
The philosophy of language is an intricate and expansive field that defies narrow definitions due to its deep entrenchment within the broader framework of philosophical inquiry. Its scope extends across nearly every domain of knowledge, making it a foundational yet complex subject of study. This article addresses the essential nature of language by treating it as a central object of philosophical investigation. The primary research question posed is: